Ácaros asociados a nidos de águila real (Aquila chrysaetos canadensis) (Falconiformes: Accipitridae) en México - Damián-Chávez, María De Jesús; Villegas-Guzmán, Gabriel A.; Lozano-Román, Luis Felipe (Instituto de Ecología, A.C., 2019)
The nests of the birds can host a great diversity of arthropods, which is a function of the composition, structure and size of the nest, as well as the activities of the bird. The most abundant component of the arthropod fauna present in the nests are the mites, which include the fauna associated with the microenvironment of the nest. The aim of the present work was to explore the richness and diversity of mites associated with the golden eagle nests and provide information on the mite-nest association. Two golden eagle nests (Aquila chysaetos canadensis) were collected on July 19, 2013 in Sierra Fría, Zacatecas (Nest I) and Juan Grande, Aguascalientes (Nest II), Mexico. All the materials of the nests were processed according to the Berlese-Tullgren funnel technique. For both nests there were 2,141 mites, belonging to 68 species of 49 families, for both nests, the adults were the best development phase, being the females the most abundant, with values of 85.57% for Nest I and 74.30% for Nest II. For the Nest I, the most abundant species was Macrocheles mexicanus (Evans & Hyatt, 1963) (Macrochelidae), with a value of 50.64%, being the females more abundant than the males. On the other hand, the most abundant species in Nest II was Eulohmannia sp. (13.61%), registering females, deutonymphs and larvae. Diversity and richness were calculated for the two golden eagle nests, where Nest II presented a higher diversity and richness of species (1-D= 0.927, ???= 7.455). This work represents a first approach to the knowledge of mites associated with golden eagle nests.